Design Engineering 2004
DOI: 10.1115/imece2004-61469
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Self-Piercing Riveting Process

Abstract: A nonlinear finite element model is built to study the self-piercing riveting process. In this model, the elasto-plastic properties of sheets and rivet, i.e., the dependency of flow stress on effective strain is considered. The adaptive meshing technology is used for the separation of sheet material. The piercing operation on two 2 m m-thick 5754-O aluminum sheets is simulated, and the results obtained are in agreement with the published experimental results. Using this method, residual stress and strain are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The HSS and UHSS specimens were subject to bond joining, [1][2] plug joining, [3] resistance spot welding, [3][4][5][6][7][8] and self-piercing rivet joining [9][10][11][12][13]. The bond joining [14,15] was performed by debonding the specimens and applying the original two-component panel adhesive supplied by the H vehicle manufacturer.…”
Section: B 22 Methodsmentioning
confidence: 99%
“…The HSS and UHSS specimens were subject to bond joining, [1][2] plug joining, [3] resistance spot welding, [3][4][5][6][7][8] and self-piercing rivet joining [9][10][11][12][13]. The bond joining [14,15] was performed by debonding the specimens and applying the original two-component panel adhesive supplied by the H vehicle manufacturer.…”
Section: B 22 Methodsmentioning
confidence: 99%
“…The method was applied to a full vehicle side impact analysis and achieved a good correlation with deformed mode and SPR separation. Sui et al (2004) built a non-linear FE model to study the SPR process and found that the hoop residual stress has the greatest influence the mechanical properties of a joint. Kim et al (2005) tried to evaluate the structural stiffness and fatigue life of SPR joint specimens, experimental and numerically (by FEM modelling in according with the FEMFAT guidelines) and found that even though the structural stiffness of an SPR joint specimen is roughly the same other types of joints (e.g.…”
Section: Finite Element Analysis Of Spr Jointsmentioning
confidence: 99%
“…Adaptive remeshing technology is used to solve this problem. 21 Full Newton-Raphson algorithm is used for the iterative procedure.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…However, with the current simulation method, the mesh used to model the materials may become highly distorted during large deformation. Adaptive remeshing technology is used to solve this problem 21. Full Newton–Raphson algorithm is used for the iterative procedure.…”
Section: Finite Element Analysismentioning
confidence: 99%